Some Reflections on the Woodhouse and ACC Legacy - Clayton, Alan (Victoria University of Wellington Law Review, 2003)
In this summary of the symposium, Alan Clayton urges New Zealanders to recognize the uniqueness and importance of the original Woodhouse vision and the resulting Accident Compensation regime, but also encourages New Zealanders to look towards improving the system. Having placed the Woodhouse vision within its historical context, the author argues that it has stood the test of subsequent developments well but he criticises the failure to properly focus on accident prevention. While he notes a recent change in both political and administrative commitment to accident prevention, he believes that there is clearly still much work to be done.